Hard carbon negative electrode material as well as preparation method and application thereof

By performing low-temperature heat treatment on waste clothes, crosslinker activation pore formation and step-by-step carbonization treatment, hard carbon negative electrode materials with excellent electrochemical properties were prepared, which solved the problems of low specific capacity and first-time Coulomb efficiency in the prior art, and significantly improved the performance of the battery.

CN119735192AActive Publication Date: 2025-04-01SHANGHAI SHANSHAN NEW MATERIAL CO LTD

Patent Information

Application Number
CN202411917658.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-04-01
Estimated Expiration
2044-12-23

AI Technical Summary

Technical Problem

In the prior art, when used clothes are prepared into hard charcoal materials, there are problems of lower specific capacity and lower Coulomb efficiency for the first time, which affects the overall performance of the battery.

Method used

The used clothes were pretreated by low-temperature heat treatment, followed by activation of pores using crosslinking agent, and then step-by-step carbonization treatment was carried out to prepare a hard carbon negative electrode material with excellent electrochemical properties.

Benefits of technology

The reversible specific capacity and first-time Coulomb efficiency of hard carbon negative electrode materials have been significantly improved, and the electrochemical performance of lithium-ion batteries and sodium-ion batteries have been improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119735192A_ABST
    Figure CN119735192A_ABST
Patent Text Reader

Abstract

The invention provides a hard carbon negative electrode material and a preparation method and application thereof, and the preparation method comprises the following steps: S1, carrying out low-temperature heat treatment on pretreated waste clothes to obtain a first precursor; the temperature of the low-temperature heat treatment is 500-800 DEG C; s2, performing activation pore-forming on the first precursor by adopting a cross-linking agent to obtain a second precursor; s3, carbonizing the second precursor to obtain a hard carbon negative electrode material; the carbonization treatment comprises first heat treatment and second heat treatment; the temperature of the first heat treatment is 500-900 DEG C, and the time of the first heat treatment is 1-6 hours; the temperature of the second heat treatment is 1200-1500 DEG C, and the time of the second heat treatment is 1-6 hours. A lithium ion battery and a sodium ion battery which are subsequently prepared from the hard carbon negative electrode material provided by the invention have excellent electrochemical performance, and the reversible specific capacity and the first coulombic efficiency of the lithium ion battery and the sodium ion battery are remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a hard carbon negative electrode material, a preparation method and application thereof. Background Art

[0002] Secondary batteries have developed rapidly in just a few decades and have been widely used in electronic products, small electronic devices, electric vehicles and energy storage. The performance of secondary batteries is mainly affected by the positive electrode, negative electrode, electrolyte and separator, among which the key to determining battery performance is the positive electrode and negative electrode materials. Among them, the important influence of negative electrode materials on batteries includes battery cycle life, energy density, power density and safety performance. Graphite is currently the most widely used negative electrode material in lithium-ion batteries due to its low working point and excellent cycle stability. However, the performance of graphite materials is infinitely close to its theoretical specific capacity, and there is limited room for improvement. At the same time, due to the large radius of sodium ions, it is difficult to embed into graphite, making it difficult for graphite to become a negative electrode material for sodium-ion batteries. Nowadays, hard carbon materials have a large number of applications in lithium battery fast charging due to their good rate performance and cycle stability, which helps to improve the performance of electric vehicles and digital products in low temperature, fast charging and cycle stability. At the same time, due to the unique bulk structure of hard carbon, it can also store a large amount of sodium ions, making it the preferred negative electrode material for sodium-ion batteries.

[0003] The amount of waste clothing to be processed in China is about 26 million tons every year. According to the China Resources Comprehensive Utilization Association, about 26 million tons of old clothes are thrown into the trash in my country every year, and the recycling rate is less than 1%. It is estimated that by 2030, this number will rise to 50 million tons, and an average of 16 pieces of waste clothing will be eliminated per person each year. If waste clothing is used as raw materials for hard carbon materials for secondary batteries after treatment, the resource utilization and reuse of waste clothing will be realized, which will have extremely high practical significance and market value. However, in the actual preparation process, the use of waste clothing to prepare hard carbon materials still has disadvantages such as low specific capacity and low first coulomb efficiency that affect the overall performance of the battery. Although at present, in the prior art, when the hard carbon material prepared from waste clothing is applied to the negative electrode of the battery, its specific capacity and first coulomb efficiency have been improved, there is still a lot of room for improvement. Summary of the invention

[0004] In order to solve the problems of low specific capacity and low initial coulombic efficiency when waste clothing is used to prepare hard carbon materials in the prior art, the present invention provides a hard carbon negative electrode material, a preparation method and application thereof. The lithium ion battery and sodium ion battery subsequently prepared from the hard carbon negative electrode material provided by the present invention have excellent electrochemical properties, and their reversible specific capacity and initial coulombic efficiency are significantly improved.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions:

[0006] The present invention provides a method for preparing a hard carbon negative electrode material, which comprises the following steps:

[0007] S1: subjecting the pretreated waste clothing to low-temperature heat treatment to obtain a first precursor;

[0008] The temperature of the low temperature heat treatment is 500°C to 800°C;

[0009] S2: activating the first precursor with a cross-linking agent to form pores to obtain a second precursor;

[0010] S3: carbonizing the second precursor to obtain a hard carbon negative electrode material;

[0011] The carbonization treatment includes a first heat treatment and a second heat treatment; the temperature of the first heat treatment is 500°C to 900°C, and the time of the first heat treatment is 1 to 6 hours; the temperature of the second heat treatment is 1200°C to 1500°C, and the time of the second heat treatment is 1 to 6 hours.

[0012] In the present invention, in step S1, the waste clothing may be one or more of cotton clothing, wool clothing, synthetic fiber clothing, leather clothing and animal wool clothing.

[0013] In some preferred embodiments, in step S1, the low-temperature heat treatment is performed in a coating kettle.

[0014] In some preferred embodiments, in step S1, the low temperature heat treatment is performed under an inert atmosphere, for example, nitrogen and / or carbon dioxide.

[0015] In some preferred embodiments, in step S1, the temperature of the low temperature heat treatment is 500-700°C.

[0016] In some preferred embodiments, in step S1, the heating rate of the low temperature heat treatment is 0.01-10°C / min, preferably 0.1-4°C / min, for example 0.5°C / min, 1°C / min or 2°C / min.

[0017] In some preferred embodiments, in step S1, the low temperature heat treatment lasts for 1 to 10 hours, preferably 4 to 6 hours, for example 4.5 hours. The low temperature heat treatment lasts for a total time of keeping warm at the temperature of the low temperature heat treatment.

[0018] In some more preferred embodiments, in step S1, the low-temperature heat treatment is performed by introducing nitrogen into the coating kettle containing the waste clothing, heating the kettle to 500°C at a rate of 2°C / min, and keeping the temperature for 4 hours.

[0019] In some more preferred embodiments, in step S1, the low-temperature heat treatment is performed by introducing nitrogen into the coating kettle containing the waste clothing, heating the kettle to 500°C at a rate of 0.5°C / min, and maintaining the temperature for 6 hours.

[0020] In some more preferred embodiments, in step S1, the operation of the low-temperature heat treatment is to first introduce a carbon dioxide / nitrogen mixture into the coating kettle containing the waste clothes, raise the temperature to 500°C at 1°C / min, and keep it warm for 0.5h, then introduce nitrogen, raise the temperature to 700°C at 2°C / min, and keep it warm for 4h.

[0021] In the present invention, in step S1, the pretreatment may include operations of crushing, demagnetizing, cleaning and pulverizing in sequence.

[0022] In some preferred embodiments, in step S1, the crushing operation is to crush the waste clothing into waste cloth strips with a length of less than 100 mm, preferably using a shearing crusher for crushing.

[0023] In some preferred embodiments, in step S1, the demagnetization operation is to remove metal foreign matter in the waste clothing, preferably using a wet demagnetization machine for demagnetization.

[0024] In some preferred embodiments, in step S1, the washing operation is to wash the waste clothes with an inorganic solvent and an organic solvent sufficient to immerse the waste clothes therein.

[0025] In the above scheme, the inorganic solvent is preferably one or both of clean water and deionized water.

[0026] In the above scheme, the organic solvent is preferably one or more of methanol, ethanol, acetonitrile, petroleum ether, ethyl acetate, dichloromethane, N-methylpyrrolidone, N,N-dimethylformamide and dimethylacetamide.

[0027] In the above scheme, the cleaning operation preferably also includes a drying operation; the drying is preferably carried out in a blast drying oven; the drying is preferably carried out under a nitrogen atmosphere; the drying temperature is preferably 70-90°C, for example: 80°C; the drying time is preferably ≥24h.

[0028] In some preferred embodiments, in step S1, the crushing operation is to Clothes first The waste clothes are roughly crushed and then finely crushed until the D50 particle size of the waste clothes is 1 to 15 μm. Preferably, it is 1 to 5 μm.

[0029] In the above scheme, the coarse crushing is preferably carried out by using a cutting type pulverizer.

[0030] In the above scheme, the fine grinding is preferably carried out by using a freezing grinder and / or a wet sand mill.

[0031] In some preferred embodiments, in step S2, the usage ratio of the first precursor to the cross-linking agent is 1:(0.5-5), for example: 1:1.2, 1:3 or 1:4.

[0032] In some preferred embodiments, in step S2, the cross-linking agent is one or more of oxygen, hydrogen peroxide, potassium permanganate, aqua regia, vinylbenzene, methyl methacrylate, vinyl acetate, diallyl phthalate, azobisisoheptanenitrile, ammonium persulfate, dicumyl peroxide, potassium persulfate, sodium persulfate, phosphoric acid, nitric acid, hydrochloric acid, sulfuric acid, acetic acid, formic acid, sodium hydroxide, potassium hydroxide, sodium bicarbonate, dimethylamine, triethylamine, aniline and diisopropylethylamine.

[0033] In some preferred embodiments, in step S2, the activation pore-forming operation is to add a cross-linking agent to the first precursor for washing, and then use deionized water to wash the material to neutrality.

[0034] In some more preferred embodiments, in step S2, the activation pore-forming operation is to first add acid solution to the first precursor for washing, and then use deionized water to wash the material to neutrality.

[0035] In the above scheme, the acid solution is preferably a mixed solution of concentrated phosphoric acid / concentrated hydrochloric acid / hydrofluoric acid, and the volume ratio of concentrated phosphoric acid, concentrated hydrochloric acid and hydrofluoric acid in the mixed solution is preferably 2:2:1.

[0036] In some more preferred embodiments, the activation pore-forming operation is to first add acid solution to the first precursor for washing, then use deionized water to wash the material to neutrality, then wash with alkaline solution, and finally use deionized water to wash the material to neutrality.

[0037] In the above scheme, the acid solution is preferably aqua regia or a mixed solution of concentrated sulfuric acid / concentrated nitric acid / concentrated hydrochloric acid, and the volume ratio of concentrated sulfuric acid, concentrated nitric acid and concentrated hydrochloric acid in the mixed solution is preferably 1:2:2.

[0038] In the above scheme, the alkali solution is preferably a potassium hydroxide solution or a sodium hydroxide solution; the concentration of the alkali solution is preferably 0.5-2 mol / L.

[0039] In the present invention, the purpose of washing with a crosslinking agent (such as acid solution) is mainly to etch and form pores on the material surface, and it also has the effect of removing impurities, that is, forming water-soluble compounds with some inorganic molecules to remove impurities during subsequent washing with deionized water.

[0040] In some more preferred embodiments, in step S2, the activation and pore-forming operation further includes a drying operation.

[0041] In the above scheme, preferably, the drying is carried out in a blast drying oven; the drying temperature is preferably 100-120°C, for example: 110°C; and the drying time is preferably ≥24h.

[0042] In the above scheme, preferably, the drying is first carried out in a blast drying oven and then in a vacuum drying oven; the drying temperature is preferably 100-120°C, for example: 110°C; the drying time is preferably ≥24h.

[0043] In the present invention, in step S3, the time of the first heat treatment and the second heat treatment are respectively the time of keeping warm at corresponding temperatures.

[0044] In some preferred embodiments, in step S3, the carbonization treatment is performed in a box-type atmosphere furnace or a tube furnace.

[0045] In some preferred embodiments, in step S3, the carbonization treatment is preferably performed under an inert atmosphere, such as nitrogen and / or argon.

[0046] In some preferred embodiments, in step S3, the heating rate of the first heat treatment is 0.01-10°C / min, preferably 1-6°C / min, for example 5°C / min.

[0047] In some preferred embodiments, in step S3, the first heat treatment is performed for 1 to 4 hours.

[0048] In some preferred embodiments, in step S3, the temperature of the second heat treatment is 1300°C.

[0049] In some preferred embodiments, in step S3, the heating rate of the second heat treatment is 0.01-10°C / min, preferably 1-4°C / min, for example 2°C / min.

[0050] In some preferred embodiments, in step S3, the second heat treatment is performed for 1 to 4 hours.

[0051] The present invention also provides a hard carbon negative electrode material, which is prepared by the preparation method of the hard carbon negative electrode material as described above;

[0052] The D50 particle size of the hard carbon negative electrode material is 1 to 15 μm.

[0053] In some preferred embodiments, the D50 particle size of the hard carbon negative electrode material is 1 to 5 μm. For example: 1.5μm, 3 μm or 4μm.

[0054] The present invention also provides a use of the hard carbon negative electrode material as described above in a lithium ion battery or a sodium ion battery.

[0055] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.

[0056] The reagents and raw materials used in the present invention are commercially available.

[0057] The positive and progressive effects of the present invention are:

[0058] (1) The hard carbon negative electrode material provided by the present invention has a good internal bulk structure, and the lithium ion batteries and sodium ion batteries prepared therefrom have excellent electrochemical properties, and their reversible specific capacity and first coulombic efficiency are significantly improved.

[0059] (2) The preparation method of the hard carbon negative electrode material provided by the present invention controls the step-by-step carbonization so that molecules with different molecular weights and boiling points can be volatilized evenly. In addition, the etching and pore formation prevents the surface of the material from being severely etched, and the surface that was etched in the early stage is also repaired after carbonization. The two work together to achieve the purpose of regulating the particle size of the hard carbon material, the degree of cross-linking of the material and the internal pore structure.

[0060] (3) The preparation method of the hard carbon negative electrode material provided by the present invention uses waste clothing as raw materials. The synthesis process is simple, safe, reliable and environmentally friendly. Compared with traditional landfill, refurbishment and recycling (with the risk of carrying pathogens), cracking and incineration, the present invention realizes the harmless reuse of waste clothing, which can save a lot of resources, reduce CO2 emissions and achieve sustainable development. BRIEF DESCRIPTION OF THE DRAWINGS

[0061] Figure 1 This is a SEM image of the hard carbon negative electrode material prepared in Example 1 of the present invention.

[0062] Figure 2 This is a pore size distribution curve of the hard carbon negative electrode material prepared in Example 1 of the present invention.

[0063] Figure 3 The charge and discharge curve of a lithium-ion battery prepared using the hard carbon negative electrode material prepared in Example 1 of the present invention.

[0064] Figure 4 The charge and discharge curve of a sodium ion battery prepared using the hard carbon negative electrode material prepared in Example 1 of the present invention.

[0065] Figure 5 This is a SEM image of the hard carbon negative electrode material prepared in Example 2 of the present invention. DETAILED DESCRIPTION

[0066] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.

[0067] Example 1

[0068] S1:

[0069] (1) crushing the waste clothes by a shearing pulverizer to obtain waste cloth strips with a length of less than 100 mm;

[0070] (2) Demagnetizing the waste cloth strips by a wet demagnetizing machine;

[0071] (3) The demagnetized waste cloth strips are washed with clean water and deionized water in amounts sufficient to immerse the waste cloth strips, and then the washed waste cloth strips are washed with ethanol, ethyl acetate, petroleum ether, and dichloromethane in amounts sufficient to immerse the waste cloth strips, and then the materials are placed in a nitrogen-protected blast drying oven at 80° C. for drying for 24 hours;

[0072] (4) The dried material is first coarsely crushed using a cutting mill, and then finely crushed using a freezing mill to form a pre-treated material with a D50 particle size of 4 μm;

[0073] (5) placing the pretreated product into a coating kettle and passing nitrogen gas for low-temperature heat treatment, wherein the final temperature of the coating kettle is 500° C., the heating rate is 2° C. / min, and the temperature is kept for 4 hours. After cooling, a first precursor is obtained;

[0074] S2:

[0075] (6) adding aqua regia to the first precursor for washing, the mass ratio of the first precursor to aqua regia is 1:1.2, then washing the filtered material with deionized water until neutral, adding 2 mol / L potassium hydroxide, and then washing the filtered material with deionized water until neutral, transferring it to a forced air drying oven, and drying it at 110° C. for 24 h to obtain a second precursor;

[0076] S3:

[0077] (7) The second precursor is placed in a box-type atmosphere furnace and subjected to two-step carbonization in a nitrogen atmosphere. The first step is to increase the temperature to 500°C at a rate of 5°C / min and keep the temperature for 1 hour. The second step is to increase the temperature to 1300°C at a rate of 2°C / min and keep the temperature for 1 hour. After natural cooling, the material is discharged to obtain a hard carbon negative electrode material.

[0078] Example 2

[0079] S1:

[0080] (1) to (3) are the same as in Example 1;

[0081] (4) The dried material was first coarsely crushed using a cutting mill, and then finely crushed using a wet sand mill to form a pre-treated material with a D50 particle size of 1.5 μm;

[0082] (5) placing the pretreated product into a coating kettle and passing nitrogen gas for low-temperature heat treatment, wherein the final temperature of the coating kettle is 500° C., the heating rate is 0.5° C. / min, and the temperature is kept for 6 hours. After cooling, a first precursor is obtained;

[0083] S2:

[0084] (6) Add a mixed solution of concentrated sulfuric acid / concentrated nitric acid / concentrated hydrochloric acid (volume ratio of 1:2:2) to the first precursor for washing, the mass ratio of the first precursor to the aforementioned mixed solution is 1:3, then wash the filtered material with deionized water until neutral, add 0.5 mol / L sodium hydroxide, wash the filtered material with deionized water until neutral, transfer it to a forced air drying oven, dry it at 110° C. for 12 h, and then vacuum dry it at 100° C. for 12 h to obtain a second precursor;

[0085] S3:

[0086] (7) The second precursor is placed in a box-type atmosphere furnace and subjected to two-step carbonization in a nitrogen atmosphere. The first step is to increase the temperature to 900°C at a rate of 5°C / min and keep the temperature for 1 hour. The second step is to increase the temperature to 1200°C at a rate of 2°C / min and keep the temperature for 4 hours. After natural cooling, the hard carbon negative electrode material is obtained.

[0087] Example 3

[0088] S1:

[0089] (1) to (2) are the same as in Example 1;

[0090] (3) The demagnetized waste cloth strips are washed with clean water and deionized water in amounts sufficient to immerse the waste cloth strips, and then the washed waste cloth strips are washed with petroleum ether, acetonitrile, dichloromethane, N-methylpyrrolidone and ethanol in amounts sufficient to immerse the waste cloth strips, and then the materials are placed in a nitrogen-protected blast drying oven at 80° C. for drying for 24 hours;

[0091] (4) The dried material is first crushed using a cutting mill, and then crushed using a cold Frozen crusher and The pre-treated product was finely crushed into a D50 particle size of 3 μm by a wet sand mill;

[0092] (5) placing the pretreated product into a coating reactor for low-temperature heat treatment, first passing a carbon dioxide / nitrogen mixed gas, raising the temperature to 500° C. at 1° C. / min, and keeping the temperature for 0.5 h, then passing nitrogen, raising the temperature to 700° C. at 2° C. / min, and keeping the temperature for 4 h, and cooling to obtain a first precursor;

[0093] S2:

[0094] (6) adding a mixed solution of concentrated phosphoric acid / concentrated hydrochloric acid / hydrofluoric acid (volume ratio of 2:2:1) to the first precursor for washing, the mass ratio of the first precursor to the aforementioned mixed solution is 1:4, then washing the filtered material with deionized water until neutral, transferring it to a forced air drying oven, drying it at 120° C. for 24 h, and then vacuum drying it at 120° C. for 12 h to obtain a second precursor;

[0095] S3:

[0096] (7) The second precursor is placed in a tubular furnace and subjected to two-step carbonization in a nitrogen atmosphere. The first step is to increase the temperature to 900°C at a rate of 5°C / min and keep the temperature for 1 hour. The second step is to increase the temperature to 1500°C at a rate of 2°C / min and keep the temperature for 1 hour. After natural cooling, the material is discharged to obtain a hard carbon negative electrode material.

[0097] Comparative Example 1

[0098] S1:

[0099] (1) to (3) are the same as in Example 1;

[0100] (4) The dried material is first coarsely crushed using a cutting mill, and then finely crushed using a freezing mill to form a pre-treated material with a D50 particle size of 4 μm;

[0101] (5) placing the pretreated product into a coating kettle and passing nitrogen gas for low-temperature heat treatment, wherein the final temperature treatment temperature of the coating kettle is 400° C., the heating rate is 2° C. / min, and the temperature is kept for 4 hours. After cooling, a first precursor is obtained;

[0102] S2:

[0103] (6) adding aqua regia to the first precursor for washing, the mass ratio of the first precursor to aqua regia being 1:1.2, then washing the filtered material with deionized water until neutral, transferring it to a forced air drying oven, and drying it at 110° C. for 24 h to obtain a second precursor;

[0104] S3:

[0105] (7) Same as Example 1.

[0106] Comparative Example 2

[0107] S1:

[0108] (1) to (4) are the same as in Example 2;

[0109] (5) placing the pretreated product into a coating kettle and passing nitrogen gas for low-temperature heat treatment, wherein the final temperature of the coating kettle is 400° C., the heating rate is 0.5° C. / min, and the temperature is kept for 4 hours. After cooling, a first precursor is obtained;

[0110] S2:

[0111] (6) Add a mixed solution of concentrated sulfuric acid / concentrated nitric acid (volume ratio of 1:2) to the first precursor for washing, the mass ratio of the first precursor to the aforementioned mixed solution is 1:3, then wash the filtered material with deionized water until neutral, add 2 mol / L potassium hydroxide, wash the filtered material with deionized water until neutral, transfer it to a forced air drying oven, and dry it at 110° C. for 24 h to obtain a second precursor;

[0112] S3:

[0113] (7) The second precursor is placed in a box-type atmosphere furnace and subjected to two-step carbonization in a nitrogen atmosphere. The first step is to increase the temperature to 900°C at a rate of 5°C / min and keep the temperature for 1 hour. The second step is to increase the temperature to 1100°C at a rate of 2°C / min and keep the temperature for 1 hour. After natural cooling, the material is discharged to obtain a hard carbon negative electrode material.

[0114] Comparative Example 3

[0115] S1:

[0116] (1) to (4) are the same as in Example 3;

[0117] (5) placing the pretreated product into a coating reactor for low-temperature heat treatment, first passing a carbon dioxide / nitrogen mixed gas, raising the temperature to 450° C. at 3° C. / min, keeping the temperature for 4 h, and cooling to obtain a first precursor;

[0118] S2:

[0119] (6) adding concentrated phosphoric acid to the first precursor for washing, the mass ratio of the first precursor to the aforementioned mixed solution is 1:4, then washing the filtered material with deionized water until neutral, transferring it to a forced air drying oven, drying it at 120° C. for 24 h, and then vacuum drying it at 180° C. for 12 h to obtain a second precursor;

[0120] S3:

[0121] (7) The second precursor is placed in a tubular furnace and carbonized in a nitrogen atmosphere. The first step is to increase the temperature to 1500°C at a rate of 5°C / min, keep the temperature for 1 hour, and then discharge the material after natural cooling to obtain a hard carbon negative electrode material.

[0122] Effect Example 1

[0123] Characterization of properties of hard carbon anode materials

[0124] (1) Test method

[0125] The present invention uses a scanning electron microscope (phenome XL) to characterize the surface morphology of the prepared hard carbon negative electrode material; the D50 particle size and pore size distribution curve of the hard carbon negative electrode material prepared by the present invention are measured by a laser particle size analyzer (Mastersize 2000).

[0126] (2) Test results

[0127] Test results such as Figure 1 , 2 and 5. Figure 1 This is a SEM image of the hard carbon negative electrode material prepared in Example 1 of the present invention; Figure 5 This is a SEM image of the hard carbon negative electrode material prepared in Example 2 of the present invention. Figure 1 and 5 As shown, the hard carbon negative electrode materials prepared in Examples 1 and 2 are both irregular black particles with uniform particles. Figure 2 The pore size distribution curve of the hard carbon negative electrode material prepared in Example 1 of the present invention is shown in FIG. Figure 2 It can be seen that hard carbon negative electrode materials have both micropores and mesopores. This wide pore size distribution is beneficial for both lithium and sodium storage.

[0128] Effect Example 2

[0129] Electrochemical performance test of batteries prepared with hard carbon negative electrode materials

[0130] (1) Test method

[0131] a. Preparation of electrodes

[0132] At room temperature, the hard carbon negative electrode materials prepared in Examples 1 to 3 and Comparative Examples 1 to 3, acetylene black conductive agent SP, and PVDF binder were mixed in a mass ratio of 8:1:1 with NMP as solvent to prepare a uniform slurry, and the slurry was evenly coated on the copper foil with a coating surface density of about 5 mg / cm 2 Then put the copper foil into a vacuum drying oven at 90℃ for 12h. Cut the dried copper foil into pieces with an area of ​​2cm 2 The disc is made into the working electrode.

[0133] b. Assembly of half-cell

[0134] At room temperature, a CR-2032 button cell was assembled in a vacuum glove box using a lithium metal sheet as a counter electrode, the product obtained in step a as a working electrode, a Celgard 2400 polypropylene porous membrane as a diaphragm, and a 1 mol / L LiPF6 in EC / DEC (EC to DEC volume ratio of 1:1) solution as an electrolyte.

[0135] At room temperature, a CR-2032 button cell was assembled in a vacuum glove box using a sodium metal sheet as a counter electrode, the product obtained in step a as a working electrode, a glass fiber membrane as a diaphragm, and a 1 mol / L NaPF6 in EC / DEC (EC to DEC volume ratio of 1:1) solution as an electrolyte.

[0136] (2) Test results

[0137] Table 1

[0138]

[0139] As can be seen from Table 1, the reversible specific capacity and the first coulombic efficiency of Examples 1 and 3 of the present invention are respectively higher than those of Comparative Examples 1 and 3. This is because the preparation method of the hard carbon negative electrode material provided by the present invention controls the step-by-step carbonization, so that molecules with different molecular weights and boiling points are uniformly volatilized, and the etching pore formation is controlled, thereby achieving the purpose of regulating the particle size of the hard carbon material, the degree of cross-linking of the material and the internal pore structure, thereby significantly improving the reversible specific capacity and the first coulombic efficiency of the hard carbon negative electrode material used in the battery.

[0140] At the same time, the hard carbon negative electrode material prepared in Example 2 of the present invention has a smaller particle size, a larger specific surface area, more surface oxygen-containing functional groups, more surface defects, more surface active sites, a more developed pore distribution, and a stronger lithium storage capacity. Compared with Comparative Example 2, it can be seen that the battery prepared with the hard carbon negative electrode material prepared in Example 2 has a higher reversible specific capacity, indicating that its lithium removal capacity is high, and it can be inferred that its lithium insertion capacity is higher, and it has good application scenarios and higher market value in the future.

[0141] The above is only the preferred specific implementation mode selected by the present invention, and the present invention includes but is not limited to the details in the above implementation mode; in order to avoid unnecessary repetition, the present invention will not go into details about other combinations, and any combination can be carried out in a suitable manner within the scope of the technical solution of the present invention; simple modifications and embellishments made by technicians familiar with the field without violating the technical essence of the present invention are deemed to be within the protection scope of the present invention.

Claims

1. A method for preparing a hard carbon negative electrode material, characterized in that: It includes the following steps: S1: subjecting the pretreated waste clothing to low-temperature heat treatment to obtain a first precursor; The temperature of the low temperature heat treatment is 500°C to 800°C; S2: activating the first precursor with a cross-linking agent to form pores to obtain a second precursor; S3: carbonizing the second precursor to obtain a hard carbon negative electrode material; The carbonization treatment includes a first heat treatment and a second heat treatment; the temperature of the first heat treatment is 500°C to 900°C, and the time of the first heat treatment is 1 to 6 hours; the temperature of the second heat treatment is 1200°C to 1500°C, and the time of the second heat treatment is 1 to 6 hours.

2. The method for preparing a hard carbon negative electrode material according to claim 1, characterized in that: In step S1, the waste clothing is one or more of cotton clothing, wool clothing, synthetic fiber clothing, leather clothing and animal wool clothing.

3. The method for preparing the hard carbon negative electrode material according to claim 1, characterized in that: It meets one or more of the following conditions: (1) In step S1, the low-temperature heat treatment is performed in a coating kettle; (2) In step S1, the low temperature heat treatment is performed under an inert atmosphere, for example, nitrogen and / or carbon dioxide; (3) In step S1, the temperature of the low temperature heat treatment is 500-700° C.; (4) In step S1, the heating rate of the low temperature heat treatment is 0.01 to 10°C / min, preferably 0.1 to 4°C / min, for example, 0.5°C / min, 1°C / min or 2°C / min; (5) In step S1, the low temperature heat treatment time is 1 to 10 hours, preferably 4 to 6 hours, for example: 4.5 hours; (6) In step S1, the low-temperature heat treatment is performed by introducing nitrogen into the coating kettle containing the waste clothing, heating the kettle at a rate of 2°C / min to 500°C, and keeping the temperature for 4 hours; (7) In step S1, the low-temperature heat treatment is performed by introducing nitrogen into the coating kettle containing the waste clothing, heating the kettle at a rate of 0.5°C / min to 500°C, and keeping the temperature for 6 hours; (8) In step S1, the low-temperature heat treatment is performed by first introducing a carbon dioxide / nitrogen mixture into the coating kettle containing the waste clothing, raising the temperature to 500°C at a rate of 1°C / min, and keeping the temperature for 0.5 h. Then, nitrogen is introduced, and the temperature is raised to 700°C at a rate of 2°C / min, and the temperature is kept for 4 h.

4. The method for preparing a hard carbon negative electrode material according to claim 1, characterized in that: The pretreatment includes crushing, demagnetization, cleaning and pulverization operations in sequence, which meet one or more of the following conditions: (1) In step S1, the crushing operation is to crush the waste clothing into waste cloth strips with a length of less than 100 mm, preferably using a shearing crusher for crushing; (2) In step S1, the demagnetization operation is to remove the metal foreign matter in the waste clothing, preferably using a wet demagnetization machine for demagnetization; (3) In step S1, the washing operation is to wash the waste clothes with an inorganic solvent and an organic solvent sufficient to immerse the waste clothes therein; Wherein, the inorganic solvent is preferably one or two of clean water and deionized water; Wherein, the organic solvent is preferably one or more of methanol, ethanol, acetonitrile, petroleum ether, ethyl acetate, dichloromethane, N-methylpyrrolidone, N,N-dimethylformamide and dimethylacetamide; The cleaning operation preferably further includes a drying operation; the drying is preferably carried out in a blast drying oven; the drying is preferably carried out under a nitrogen atmosphere; the drying temperature is preferably 70 to 90° C., for example, 80° C.; the drying time is preferably ≥ 24 hours; (4) In step S1, the crushing operation is to first coarsely crush the waste clothes and then finely crush them until the D50 particle size of the waste clothes is 1 to 15 μm, preferably 1 to 5 μm; Wherein, the coarse crushing is preferably carried out by using a shearing type pulverizer; Wherein, the fine grinding is preferably carried out by using a freezing grinder and / or a wet sand mill.

5. The method for preparing a hard carbon negative electrode material according to claim 1, characterized in that: It meets one or more of the following conditions: (1) In step S2, the ratio of the first precursor to the cross-linking agent is 1:(0.5-5), for example: 1:1.2, 1:3 or 1:4; (2) In step S2, the crosslinking agent is one or more of oxygen, hydrogen peroxide, potassium permanganate, aqua regia, vinylbenzene, methyl methacrylate, vinyl acetate, diallyl phthalate, azobisisoheptanenitrile, ammonium persulfate, dicumyl peroxide, potassium persulfate, sodium persulfate, phosphoric acid, nitric acid, hydrochloric acid, sulfuric acid, acetic acid, formic acid, sodium hydroxide, potassium hydroxide, sodium bicarbonate, dimethylamine, triethylamine, aniline and diisopropylethylamine; (3) In step S2, the activation and pore-forming operation is to add a cross-linking agent to the first precursor for washing, and then use deionized water to wash the material to neutrality.

6. The method for preparing a hard carbon negative electrode material according to claim 5, characterized in that: It meets one or more of the following conditions: (1) In step S2, the activation pore-forming operation is to first add an acid solution to the first precursor for washing, and then use deionized water to wash the material to neutrality; Wherein, the acid solution is preferably a mixed solution of concentrated phosphoric acid / concentrated hydrochloric acid / hydrofluoric acid, and the volume ratio of concentrated phosphoric acid, concentrated hydrochloric acid and hydrofluoric acid in the mixed solution is preferably 2:2:1; (2) In step S2, the activation pore-forming operation is to first add an acid solution to the first precursor for washing, then use deionized water to wash the material to neutrality, then use an alkali solution to wash, and finally use deionized water to wash the material to neutrality; Wherein, the acid solution is preferably aqua regia or a mixed solution of concentrated sulfuric acid / concentrated nitric acid / concentrated hydrochloric acid, and the volume ratio of concentrated sulfuric acid, concentrated nitric acid and concentrated hydrochloric acid in the mixed solution is preferably 1:2:2; Wherein, the alkali solution is preferably a potassium hydroxide solution or a sodium hydroxide solution; the concentration of the alkali solution is preferably 0.5 to 2 mol / L; (3) In step S2, the activation and pore-forming operation also includes a drying operation; Preferably, the drying is carried out in a blast drying oven; the drying temperature is preferably 100-120°C, for example, 110°C; the drying time is preferably ≥24h; Preferably, the drying is first carried out in a blast drying oven and then in a vacuum drying oven; the drying temperature is preferably 100-120°C, for example 110°C; and the drying time is preferably ≥24h.

7. The method for preparing a hard carbon negative electrode material according to claim 1, characterized in that: It meets one or more of the following conditions: (1) In step S3, the carbonization treatment is carried out in a box-type atmosphere furnace or a tube furnace; (2) In step S3, the carbonization treatment is performed under an inert atmosphere, for example, nitrogen and / or argon; (3) In step S3, the heating rate of the first heat treatment is 0.01 to 10°C / min, preferably 1 to 6°C / min, for example 5°C / min; (4) In step S3, the first heat treatment time is 1 to 4 hours; (5) In step S3, the temperature of the second heat treatment is 1300° C.; (6) In step S3, the heating rate of the second heat treatment is 0.01 to 10°C / min, preferably 1 to 4°C / min, for example 2°C / min; (7) In step S3, the second heat treatment time is 1 to 4 hours.

8. A hard carbon negative electrode material, characterized in that: It is prepared by the method for preparing the hard carbon negative electrode material according to any one of claims 1 to 7; The D50 particle size of the hard carbon negative electrode material is 1 to 15 μm.

9. The hard carbon negative electrode material according to claim 8, characterized in that The D50 particle size of the hard carbon negative electrode material is 1 to 5 μm, for example, 1.5 μm, 3 μm or 4 μm.

10. Use of the hard carbon negative electrode material according to claim 8 or 9 in a lithium ion battery or a sodium ion battery.

Citation Information

Patent Citations

  • Hard carbon material and preparation method thereof, negative electrode material and alkali metal ion battery

    CN116692830A

  • Preparation method of sodium ion battery hard carbon-based negative electrode material based on waste fabric recycling

    CN116705999A

  • Preparation method of hard carbon negative electrode material of sodium ion battery

    CN117466276A

  • Hard carbon material, preparation method and application thereof, and battery

    CN117735522A

  • Hard carbon composite material and preparation method and application thereof

    CN117902575A

Cited By

  • Method for preparing sodium-ion battery hard carbon negative electrode material through microbial degradation of biomass

    CN121405070A